Documentation of the Genocide of the Roma during the Second World War in Czechoslovakia - Finding Report: discontinuity and continuity in the exploration of Roma history after 1946 - Závodská, Milada; Viková, Lada (Romano džaniben, 2016)
The text is significant in that it was the first to draw attention to the availability and importance of extensive archival materials on the topic of the genocide of the Roma during World War II, including the continuity of historical development within the war-decimated Roma population after 1945 in Czechoslovakia. As a finding report opened new research possibilities tied to these materials. The authors of the text comprehensively describe the complementarity of large number of official documents created between 1948 and 2006 (or nearly 2016), mainly in connection with Czechoslovakian Act no. 255/1946 (Collection of laws of the CSR), subsequently archived separately in two, or rather three, different archival institutions. These resources contain testimonies of concentration camp prisoners -- i.e. so-called "requests for certification" under Act no. 255/1946, deposited in Military History Archive (Vojenský historický archiv, Prague). It also highlights their mutual compatibility with questionnaires and requests for compensation for (so-called) "pseudo-medical"/ "criminal-medical" experiments perpetrated on prisoners by Nazi doctors, which as agenda of Union of Anti-Fascist Fighters (Svaz protifašistických bojovníků) from period 1961-1971 are deposited in National Archives (Národní archiv, Prague). And it also states that a significant part of these documents is preserved in the Moravian Provincial Archive (Moravský zemský archiv, Brno) as a correspondence and other documentation in the funds of the Union of Gypsies-Roma (Svaz Cikánů-Romů) from 1969--1973. One of the conclusions of this finding report is that the Union of Gypsies-Roma undoubtedly had the important role in the process of revealing the extent of the Romani genocide, as well as in the after war process of recognition of Romani victims in public sphere (not only in Czechoslovakia, also world-wide).
Keywords: Compensation; criminal medical experiments; Czechoslovakia; genocide; Law 255/1946; Holocaust; racial persecution; reparations; Union of Gypsies-Roma; WWII